STIE Bima Kampus Berdampak : Pendampingan Transformasi Tugas Akhir untuk Mendukung Publikasi Ilmiah Mahasiswa - Muniarty, Puji; Ovriyadin, Ovriyadin; Dwiriansyah, M Syukur (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Impactful Campus Program at the Sekolah Tinggi Ilmu Ekonomi Bima is a strategic effort to improve students' academic quality through structured final project mentoring by supervisors. This activity aims to strengthen students' abilities in compiling scientific papers that are systematic, critical, and in accordance with research methodology principles. Mentoring is carried out intensively, starting from the title determination stage, compiling the final project into a worksheet template, collecting and analyzing data, and writing articles according to journal templates. The community service approach uses a participatory, educational approach and continuous mentoring through the preparation, implementation, evaluation, and follow-up stages. The results of this program show an increase in students' understanding of research concepts, accuracy in the use of methods, and better quality scientific writing. In addition, this mentoring also encourages students to produce outputs in the form of scientific articles that have the potential to be published. Thus, this program makes a real contribution to supporting the achievement of graduate competencies that are superior, adaptive, and competitive in academic and professional environments.